PROFESSIONALISM, INTERNAL CONTROL SYSTEM, INNOVATION, AND PERFORMANCE OF REGIONAL GOVERNMENT IN INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Research on government performance is growing, but research on the professionalism of State Civil Apparatus (ASN), internal control systems, and innovation on local government performance is still rarely conducted. This research was conducted to determine the influence of ASN professionalism, internal control systems, and innovation on the performance of local governments in Indonesia. This research used secondary data with a purposive sampling method. The sample used was 490 district/city governments in Indonesia in 2021. The results of this research are that ASN professionalism, internal control systems, and innovation have a positive influence on government performance. This research implied that by knowing the effect of ASN professionalism, internal control systems, and innovation on performance, regional governments can carry out evaluations so that they can make better policies, strategies, and implementation to create government administration that is efficient, effective, beneficial to the public and regional development and motivate local governments to provide the best for the public.
Keywords: government performance; professionalism; internal control; innovation